IMPLEMENTASI KEBIJAKAN PENGELOLAAN DAERAH ALIRAN SUNGAI TONDANO DI PROVINSI SULAWESI UTARA - KAROUW, AMELIA; LIANDO, DAUD; WALELENG, GRACE (Sam Ratulangi University, 2019)
This study aims to analyze the implementation of the Tondano Watershed Management Policy in theprovince of North Sulawesi. This research uses the descriptive qualitative method. Research data are obtainedfrom informants who are representatives of the society and government. The result of the study indicatesthat on the organizational aspect, Tondano watershed management institutions are very stronglysupported by regulations under a strict legal umbrella for the management of the Tondano watershed,such as Law No. 41 1999 concerning Forestry, PP 37 2012 concerning watershed management, which issubsequently elaborated by North Sulawesi Provincial Regulation No. 1 2013 concerning the managementof the Tondano watershed. In addition to that, Tondano watershed management involves many parties(multidisciplinary and multi-sector) in the Tondano watershed area. In the aspects of interpretation policyregarding the management of the Tondano watershed, it can be concluded that the implementor andstakeholders are able to master and know their duties and functions in the management of the Tondanowatershed. In the aspect of application or implementation of Tondano watershed management policiesbased on existing regulations, however, a lot of plans in the form of programs and activities have been seenexisting in every relevant agency, all of which are to make the Tondano watershed useful and sustainable.But in their implementation, these activities have not been carried out thoroughly by the regionalgovernment both in the province and district/city. The obstacle faced is the lack of commitment andpresence of stakeholders in implementing watershed management based on existing regulations.Keywords: policy implementation, Tondano watershed management, organization, interpretation,application.